Hubungan Metode Bercerita dengan Minat Belajar Anak Usia Dini - Siti Wahyuni; Faridatul Munawaroh (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2021)
Interest is a feeling of attraction or preference for something that does not appear suddenly. The success of a learning process is often seen in students who are enthusiastic about completing given tasks and doing what they love. Students’ interest in a learning process depends on the approach and the method that the teacher provides for stimulation, one of which can be done is the storytelling method. Accordingly, this study aims to find the relationship between the storytelling method and the learning interest of early childhood. This study uses a quantitative approach. Subjects in this study were 58 teachers and students. Data collection techniques using observation and documentation, then analyzed using the product-moment correlation formula. The results showed that there was a positive relationship between the storytelling method and learning interest of early childhood, as indicated by tcount ttable (25.64 > 2.00324). It means that 25.64 ³ 2.00324 then Ho is rejected, the number 25.64 lies in the rejection area, Ha is accepted.